Genealogy of Soekarno's syncretic-eclectic thought: the intersection of culture values, religion, and ideology (1916-1926) - Fauzian Aulia Muslim; Yety Rochwulaningsih; Sri Sudarsih (Harmoni Sosial: Jurnal Pendidikan IPS, 2025)
This study aims to analyze the dynamics of values and ideas that shaped Soekarno's syncretic and eclectic thinking. This study uses a historical method that includes four stages, namely heuristics, criticism, interpretation, and historiography. Through comparative analysis, it is shown that there are differences between the concepts of syncretism and eclecticism. Eclecticism is an approach to thinking that selectively combines various elements of thought from different systems of thought. This differs from syncretism, which tends to combine elements of values and thoughts into a unity with traces of contradiction within it. The results of this study show that Soekarno's syncretic thinking was born from an active dialectical process between tradition, values, and philosophy. The intersection of Javanese values, Theosophy, Abangan Islam, and Hinduism became the foundation for the formation of Soekarno's moral horizon, which was oriented towards the idea of unity. Meanwhile, Soekarno's eclecticism was the result of his adaptation of HOS Tjokroaminoto's eclectic style of thinking, as reflected in his writings on Islam and Socialism. Tjokroaminoto selected concepts of socialism that were compatible with the framework of Islam, rather than accepting the doctrine of socialism. Based on this approach, Soekarno formulated syncretic and eclectic ideological ideas in his 1926 writing Nationalism, Islamism, and Marxism. The uniqueness of this study lies in the position of syncretism as Soekarno's moral philosophy and eclecticism as Soekarno's epistemology